TOU 11 Introduction to tourism : study guide - Baker, Janet; Spearritt, Peter, 1949-; Arnold, John, 1950 (February 6)- (Open Learning, [National Centre for Australian Studies,] Monash [University, 1996)
Provides "a general overview of [the] industry in the Australian context, with emphasis on the cultural and economic importance of tourism, the variety of destinations and patterns of tourism, and the motivation for travel." Also investigates "a range of the major contemporary issues surrounding tourism. These range from resort development, special events, the nature and significance of cultural issues and eco-tourism, to the structure of the domestic and international tourist industry"--Introd.